(untitled) (ҚазҰУ Хабаршысы. Филология сериясы, 2015)
The article On Types of Connected Syntactical Ties in Diplomatic Documents (based on examples from charters, memorandums and agreements) deals with types of lexical ties in the texts of diplomatic documents. As an factual material, charters, memorandums and agreements of GUUAM states are analyzed in the article. The texts of diplomatic documents are viewed from their syntactical structure. The syntax of diplomatic documents is quite different from the that of other texts. It has its peculiarities which differentiate it from other texts.